ASI DAN MENYUSUI (TINJAUAN DEMOGRAFI KEPENDUDUKAN - Falikhah, Nur (Alhadharah: Jurnal Ilmu Dakwah, 2014)
Breast milk is the best food for babies. Breast milk with various benefits should be the first choice for infants worldwide. However, the lack of information, knowledge level is low, poverty, lack of support from various parties and incessant advertisements about infant formula in the media make the milk of choice for so many. Breastfeeding plays an important role in improving the health of babies. With breastfeeding, children are able to pass through fifth birthday. This is because breast milk is able to improve the health of babies and to prevent from infections, diseases that cause death